KORELASI ANTARA PENGENDALIAN KUALITAS RENCANA PELAKSANAAN DENGAN KINERJA PROYEK KONSTRUKSI (Studi Kasus Pada Satuan Kerja Non Vertikal Tertentu Pengembangan Kinerja Pengelolaan Air Minum Provinsi Nusa Tenggara Timur) - Yansen, Wayan (Jurnal Ilmiah Teknik Sipil; Vol. 14, No. 2 Juli 2010, 2012)
In the construction project activity, planning is used as a reference by the implementation unit and become a standard of the project implementation, and includes: technical specifications, schedule and budgeting. Inaccurate planning, imperfect investigation of the project location, lack of experience and ability in managing the project and lack of professionalism of the service provider are closely linked to the result of the process of a construction project (project performance). This research is conducted within the physical activity scope/construction stage that aims to find out the relation between influence quality control of the implementation plan and the performance of the construction project (cost and time performances). Primary data is obtained from questionnaries and is analyzed using SPSS. The research found that the regression model chosen is nonlinear regression model where the equation Y1=1,122+0.282X1+0,208X3+0,292X15+0,325X19+0,318X9 and Y2=1,187+0.395X2+0,310X5+0,263X16+0,196X6+0,247X11 is for cost factor and time factor respectively. The coefficients found in each regression model have positive value. This shows that there is positive correlation between quality control of the implementation plan and the construction project performance. Factors affecting the cost performances are quality of planning resources for drawing design, quality of bidding of the service provider, quality control of service provider resources, the design revision, the project controlling while for the time performances there are quality of design drawing, quality of technical bidding contractors, quality of the project controlling, quality of service provider resources, and project implementation planning.
Keywords: Nonlinear regression model, Cost performance, Time performance.